2016
DOI: 10.1515/agp-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

New moldavites from SW Poland

Abstract: Large impact craters are relatively rare in geological record on the Earth. All over the world only 164 crater structures are above 1 km in diameter and only 40 with with more than 20 km in diameter (Earth Impact Database). The most notable features of such big impacts are significant pressure and temperature caused by extraterrestrial body fall. In some cases, impact may lead to glass production, which is named tektite. The distribution and chemical features of impact glasses are the most diagnostic features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The Ries crater was produced by the impact of an asteroid that was probably 1.5 km in diameter (STÖFFLER et al, 2002). European tektites originated from the melting of the uppermost sedimentary target rocks that belong to the Upper Freshwater Molasse, which overlies the Swabian-Franconian Alb plateau (MEISEL et al, 1997;TRNKA and HOUZAR, 2002;ŘANDA et al, 2008;MAGNA et al, 2011; BRACHANIEC et al, 2014bBRACHANIEC et al, , 2015BRACHANIEC et al, , 2016, and this study). B. and C. General view of the Gozdnica Formation in the western part of the Nowa Wieś Kącka sandpit.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…The Ries crater was produced by the impact of an asteroid that was probably 1.5 km in diameter (STÖFFLER et al, 2002). European tektites originated from the melting of the uppermost sedimentary target rocks that belong to the Upper Freshwater Molasse, which overlies the Swabian-Franconian Alb plateau (MEISEL et al, 1997;TRNKA and HOUZAR, 2002;ŘANDA et al, 2008;MAGNA et al, 2011; BRACHANIEC et al, 2014bBRACHANIEC et al, , 2015BRACHANIEC et al, , 2016, and this study). B. and C. General view of the Gozdnica Formation in the western part of the Nowa Wieś Kącka sandpit.…”
Section: Introductionmentioning
confidence: 57%
“…Additionally, the small amount of gravel in deposits and paleoriver meanders of the Gozdnica Formation, along with some low- Table 2. Chemical composition (based on electron microprobe analysis) of Polish moldavites from all known localities; *data from BRACHANIEC et al (2015), ** data from BRACHANIEC et al (2016), *** this study, **** LANGE (1995). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on paleogeographical reconstruction and from the Polish tektite size, Brachaniec et al. (, , ) concluded that they originated from Lusatia. In order to test this suggested long‐distance moldavite transport, tumbling experiments were conducted.…”
Section: Introductionmentioning
confidence: 99%